Catalytic routes to convert saccharides to furanic aldehydes - Antunes, Maria Margarida Feitor Pintão Moreno (2012)
The conversion of plant biomass-derived carbohydrates (preferably non-edible) into added-value products is envisaged to be at the core of the future biorefineries. Carbohydrates are the most abundant natural organic polymers on Earth. This work deals with the chemical valorisation of plant biomass, focusing on the acid-catalysed conversion of carbohydrates (mono and polysaccharides) to furanic aldehydes, namely 2-furaldehyde (Fur) and 5-hydroxymethyl-2-furaldehyde (Hmf), which are valuable platform chemicals that have the potential to replace a variety of oil derived chemicals and materials. The investigated reaction systems can be divided into two types depending on the solvent used to dissolve the carbohydrates in the reaction medium: water or ionic liquid-based systems. The reaction temperatures were greater than 150 ºC when the solvent was water, and lower than 150 º C in the cases of the ionic liquid-based catalytic systems. As alternatives to liquid acids (typically used in the industrial production of Fur), solid acid catalysts were investigated in these reaction systems. Aiming at the identification of (soluble and insoluble) reaction products, complementary characterisation techniques were used namely, FT-IR spectroscopy, liquid and solid state NMR spectroscopy, TGA, DSC and GC´GC-ToFMS analyses. Complex mixtures of soluble reaction products were obtained and different types of side reactions may occur. The requirements to be put on the catalysts for these reaction systems partly depend on the type of carbohydrates to be converted and the reaction conditions used. The thermal stability is important due to the fact that formation of humins and catalyst coking phenomena are characteristically inherent to these types of reactions systems leading to the need to regenerate the catalyst which can be effectively accomplished by calcination. Special attention was given to fully inorganic nanoporous solid acids, amorphous or crystalline, and consisting of nano to micro-size particles. The investigated catalysts were silicoaluminophosphates, aluminosilicates and zirconium-tungsten mixed oxides which are versatile catalysts in that their physicochemical properties can be fine-tuned to improve the catalytic performances in the conversion of different substrates (e.g. introduction of mesoporosity and modification of the acid properties). The catalytic systems consisting of aluminosilicates as solid acids and water as solvent seem to be more effective in converting pentoses and related polysaccharides into Fur, than hexoses and related polysaccharides into Hmf. The investigated solid acids exhibited fairly good hydrothermal stabilities. On the other hand, ionic liquid-based catalytic systems can allow reaching simultaneously high Fur and Hmf yields, particularly when Hmf is obtained from D-fructose and related polysaccharides; however, catalyst deactivation occurs and the catalytic reactions take place in homogeneous phase. As pointed out in a review of the state of the art on this topic, the development of truly heterogeneous ionic liquid-based catalytic systems for producing Fur and Hmf in high yields remains a challenge.